Attitude of health care workers in the field of mental health to their health - Chorna, V.V.; Makhniuk , V.M.; Khliestova, S.S.; Gumeniuk , N.I.; Chaika , H.V. (Medicni Perspektivi, 2021)
The article presents the results of theoretical and experimental studies of the degrees of value-motivational, cognitive, emotional, and behavioral components in health care workers of psychiatric health care facilities concerning their health. The degree of risk and value of the personal hygiene of health care workers is determined. The main components and factors that affect the attitude to personal health are revealed. The awareness of the own emotional and cognitive experiences by the medical staff of psychiatric hospitals regarding the preservation and strengthening of their hygiene is analyzed. According to research on the value-motivational component of the medical staff of psychiatric health care concerning the place of personal health in the hierarchy of values in life, it was found that own health is on the second place – 15.2% males, nursing staff (NS), 15.1% females, are psychiatrists and women NS, 14.8% are men psychiatrists. In case of a deterioration of own health both women (35,6%), and men (35,5%) psychiatrists are engaged in self-treatment, the similar tendency is among NS – women NS – 31,3%, men NS – 31, 5%), in 25.8% of cases female psychiatrists and in 23.1% of men NS do not pay attention to the disease at all, which leads to occupational diseases and chronic diseases. At the same time, occupational diseases among doctors and NS do not exceed 10% of the total number of occupational diseases in Ukraine due to self-medication and early treatment. Therefore, the statistics of occupational diseases of health workers in that field are underestimated compared to the actual ones.